Individual- and School-level Predictors of Latent Profiles of Bullying Victimization: Comparing South Korea and the United States - Han, Yoonsun (Journal of interpersonal violence, 2022)
This cross-national research investigated nationally representative adolescents from South Korea and the United States, explored similarities and differences in latent profiles of bullying victimization between countries, and examined individual- and school-level variables that predict such latent profiles supported by the Social Disorganization Theory. The fourth-grade sample of the 2015 Trends in International Mathematics and Science Study from South Korea (N?=?4,669) and the United States (N?=?10,029) was used to conduct a latent profile analysis based on eight items of the bullying victimization questionnaire. Multilevel logistic regression was conducted using latent profiles as dependent variables. Independent variables include individual-level (material goods, school absence, academic interest, school belonging) and school-level (concentration of affluent families, school resources, the severity of delinquency, academic commitment) factors. More similarities existed than differences in the latent groups of bullying victimization between South Korea (rare, low-moderate, verbal-relational-physical, and multi-risk) and the United States (rare, low-moderate, verbal-relational, and multi-risk). Evidence for school-level variables as predictors of bullying victimization profiles was stronger for adolescents in the United States, with a concentration of affluent families and severity of delinquency being significant in four of the six models. For the South Korean sample, the severity of delinquency predicted bullying victimization in only one model. Examination of both individual- and school-level factors that predict unique bullying victimization experiences grounded in Social Disorganization Theory may be informative for addressing key areas of intervention?especially at the school-level context in which victimization primarily takes place and where anti-bullying intervention programs are often provided.